Washington View: Choice for Secretary of Education. (February 2017) - Ferguson, Maria
Betsy DeVos, the new Secretary of Education, comes to the job with hopes of creating school voucher programs and expanding the charter school sector. But she will likely find that she has limited power to promote that agenda. While she may be able to convince some states to launch modest new voucher experiments and while she can take advantage of her bully pulpit to advocate on behalf of the charter movement, she inherits an office that — thanks to the Every Student Succeeds Act — gives her far less influence over educational policy making than her predecessors enjoyed .